Effectiveness of an Intervention Program Based on Mindfulness to Self-Regulate Care in Primary School Children - González-Cortez, Nicol Andrea; Lagos-San Martín, Nelly Gromiria (Revista Electrónica Educare, 2022)
The literature states that attention is inherent to learning so that, if attention is altered, the entry and focus of the various experiences would have a limited extent. It is also affirmed that if attention was properly stimulated, the enrichment of the experiences would be enormously fruitful. Due to the importance of considering attention as a formative process, this study has designed a program based on mindfulness guidelines to strengthen the self-regulation of attention in basic education children and the evaluation of its effectiveness in developing focused, sustained, and divided attention. For this purpose, a sample of 46 children from the third grade of elementary school in Pemuco, Chile, aged between 8 and 9 years old, was selected. The focus of the study is of a sequential testing type, framed in a Pre-post test design with a control group. In the control and experimental group, the dependent variable was measured using the CARAS test, the CLAVES sub-scale of the WISC-III test, and the CSAT test. The results show a significant increase in the self-control of the intervention group compared to the control group, endorsing the impact of this tool that is made available to the education system as an effective program for the strengthening of attentional self-regulation.